A low-cost and efficient cloud monitoring camera system design for imaging satellites. Issue 7 (3rd April 2019) - Vala, Alpesh; Patel, Amit; Gosai, Riddhi; Chaudharia, Jitendra; Mewada, Hiren; Mahant, Keyur
ABSTRACT: Design and development of a cloud monitoring camera (CMC) as a secondary camera for imaging/remote-sensing satellites is proposed here. It is well known that presence of clouds alters the earth-atmospheree energy budget by scattering and absorbing the shortwave radiation and absorbing and re-emitting the infrared radiation. Detection of clouds at precise positions, prior to the initiation of the imaging session of the primary (super resolution) camera can aid in saving power as well as memory storage of the satellite. Key feature of the proposed system is the implementation of an onboard cloud detection system in the visible band. The proposed system is miniature in size and cost-effective when compared to the existing integrated visible and infrared band detection system. It primarily consists of lens assembly, detector head assembly, field programmable gate array (FPGA)-based camera electronics system with supporting proximity electronics. Cloud detection algorithm for the visible band images is derived and simulated with the help of Laboratory Virtual Instrument Engineering Workbench software. The verification and hardware realization of the algorithm is achieved by implementing it on a FPGA-based system. Overall simulated and measured efficiency of more than 94% was achieved. The volume of the system is 85 mm × 85 mm × 25 mm and weighs approximately 2 kg, making it suitable for satellite mounting.